(untitled) (Biological Sciences - PJSIR, 1994)
In the Dau Dam silica sand deposits, the main impurity is iron, present as heavy black particles of magnetic and hornblende and yellow to reddish coatings of limonite on some of the grains. Simple beneficiation methods of water washing, screening and dry magnetic separation render these sands suitable for the manufacture of glass.